Motives for coffee consumption at coffee shops in Mexico - Espinoza-Ortega, Angélica; Cruz-Flores, Maryan; Thomé-Ortiz, Humberto; Vizcarra-Bordia, Ivonne (Coffee Science - ISSN 1984-3909, 2020)
Coffee is one of the main sources of foreign exchange for developing countries. Mexico accounts only 2.68% of the world coffee production, but represent the most important source of foreign exchange in the agricultural sector. The Mexican coffee began to be recognized in recent years, and despite the increase of the consumption, Mexico is not considered an important consumer. The objective was to analyse the motives for coffee consumption at coffee shops with quality labels. A national and a transnational company were selected in central Mexico to carry out a total of 600 questionnaires. The questionnaire had four sections: frequency of consumption, Food Choice Questionnaire (FCQ), some images of coffee quality labels, and a socio-economic. The data were analysed using multivariate statistics, factor and cluster analysis. Indifferent, Pragmatic and Hedonic-Dependent consumers were identified; who are mostly young and middle-aged, single, childless and college educated. Their interest in attending coffee shops is to socialize; they are not interested in quality labels which have negative implications for the use of this type of labels in Mexico. Key words: Consumers; food choice questionnaire; factor and cluster analysis.